CONSUMER DECISION MAKING IN CHANGING DEBIT CARD FROM VISA OR MASTERCARD INTO GPN (GERBANG PEMBAYARAN NASIONAL) - Faizal Haris Eko Prabowo; Nuryanti Taufik; Jacobus Cliff Diky Rijoly (Unitri Press, 2022)
The existence of the fourth industrial revolution made the whole way of banking work a little changed. From these events, the government and the central bank took advantage of this opportunity to create a debit card that has the same function as a visa and mastercard but originated from Indonesia. The inefficiency of the velocity of money that must be paid to foreign companies makes them act and take the decision to issue a debit card with a gerbang pembayaran nasional brand. The purpose of this study is to uncover what factors are causing customers to change their cards from visa or mastercard to GPN. The method used in this study is a survey with a quantitative approach. The population in this study amounted to 978, while the sample chosen was 211. The data used in this study were primary data obtained from questionnaires. The subjects in this study were customers who had a visa or mastercard debit card which eventually changed to GPN. The research sites were conducted in East Priangan city and regency namely Tasikmalaya City, Tasikmalaya Regency and Ciamis Regency. Data analysis techniques in this study used structural equation modeling (SEM). The results revealed that there were two variables that had an influence on the customer's decision to replace their debit cards namely word of mouth and brand awareness, while the two other variables that had no influence were customer value and price. The strategy undertaken by the government and the central bank is effective enough to stimulate customers in replacing their debit cards into GPN, by making GPN a news that is always being talked about and the intensity of GPN campaigns or promotions that are spread across every bank.